2018
DOI: 10.1021/acs.langmuir.7b03560
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Interactions and Organization at the Gas–Water Interface (CTAB with Added Salt)

Abstract: We have studied adsorbed layers of cetyltrimethylammonium bromide (CTAB) at air-water interfaces in the presence of added electrolyte. Fast bubble compression/expansion measurements were used to obtain the surface equation of state, i.e., the surface tension vs CTAB surface concentration dependence. We show that while a simple model where the surfactant molecules are assumed to be noninteracting is insufficient to describe the measured response of the surfactant layer, a modified Frumkin equation where the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 72 publications
2
34
0
Order By: Relevance
“…with the Helmholtz free energy F 0 of the repulsive 2D reference system described by U 0 = U rep , while r 2 (r,r 0 ;l) is the pair areal density of the system in which particles interact with U l according to eqn (23). This pair density is not known in general for inhomogeneous systems, 43,44 but it is related to the radial distribution function g(r,r 0 ;l) through r 2 (r,r 0 ;l) = g(r,r 0 ;l)r(r)r(r 0 ) and within the random phase approximation (RPA) [43][44][45][46][47] given by…”
Section: Density-functional Theory (Dft)mentioning
confidence: 99%
See 1 more Smart Citation
“…with the Helmholtz free energy F 0 of the repulsive 2D reference system described by U 0 = U rep , while r 2 (r,r 0 ;l) is the pair areal density of the system in which particles interact with U l according to eqn (23). This pair density is not known in general for inhomogeneous systems, 43,44 but it is related to the radial distribution function g(r,r 0 ;l) through r 2 (r,r 0 ;l) = g(r,r 0 ;l)r(r)r(r 0 ) and within the random phase approximation (RPA) [43][44][45][46][47] given by…”
Section: Density-functional Theory (Dft)mentioning
confidence: 99%
“…2,9,20 Theoretical frameworks such as Landau theory of phase transitions have been used with some success in predicting condensed phases and coexistence boundaries of Langmuir monolayers 21 qualitatively. Molecular dynamics (MD) and Monte Carlo (MC) simulations 1,2,8,10,[22][23][24] of the full 3D system including the liquid phase do not only provide more quantitative information but have also broadened our insight into the structure and phase behavior of Langmuir monolayers. Current state-of-the-art atomistic simulations 25 were so far successful in predicting the structure of gas and solid phases of phospholipid Langmuir monolayers (76 nm 2 in size, with 76 to 144 surfactants at each interface).…”
Section: Introductionmentioning
confidence: 99%
“…9 This finding is consistent with the work of Yazhgur and co-workers: they have shown that CTAB monolayers are disordered, with a significant portion lying in the plane of the monolayer-water interface even at higher packing densities than those considered in this work. 34 The monolayer roughness also increases with decreasing A CTAB (increased packing density). There are clear differences between the roughness of the monolayers in the two asymmetric systems, most notably in ASYM2, in which the difference in A CTAB of the two monolayers is greater.…”
Section: Resultsmentioning
confidence: 98%
“…Figures 1(a) and (b) highlight the roughness and patchiness of the CTAB monolayers, as previously observed in studies of CTAB monolayers at the air-water interface. 19,34 These two characteristics present a challenge when analyzing the structure of the confined water layer:…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation